Antitumor effects and hematotoxicity of C60-Cis-Pt nanocomplex in mice with Lewis lung carcinoma - Prylutska, S.V.; Lynchak, O.V.; Kostjukov, V.V.; Evstigneev, M.P.; Remeniak, O.V.; Rybalchenko, V.K.; Prylutskyy, Yu.I.; Ritter, U.; Scharff, P. (PH Akademperiodyka, 2023)
Summary. Background: Cisplatin (Cis-Pt) is a widely used anticancer drug but its therapeutic efficiency is limited by hemato-, cardio-, hepato-, nephro- and neurotoxicity. Complexation of Cis-Pt with C60 fullerene nanoparticle will allow to enhance the antitumor activity of the drug and to reduce its side toxic effects. Aim: To estimate the antitumor effects of С60-Cis-Pt nanocomplex in Lewis lung carcinoma (LLC) and analyze hematological toxicity in tumor-bearing mice. Materials and Methods: Complexation of C60 fullerene and Cis-Pt molecule was studied by computer simulation. С60-Cis-Pt nanocomplex was i.p. injected to LLC-bearing mice in a total dose of 7.5 mg/kg (C60:Cis-Pt as 3.75:3.75 mg/kg). The survival of tumor-bearing mice and the relative reduction of tumor weight was recorded. Blood indices were determined using the Particle Counter PCE210 automatic hematology analyzer. Results: Computer simulation demonstrated the formation of С60-Cis-Pt nanocomplex in physiological medium and its stability due to the hydrophobic interactions. Treatment with C60-Cis-Pt nanocomplex increased survival time of LLC-bearing mice by 32%, normalized hemoglobin content (up to 100 g/l), erythrocyte and platelet count as compared to the untreated LLC-bearing mice. Tumor weight decreased by 35.5%; the mitotic index of tumor cells decreased by 78%, and apoptotic index increased by 75%. The revealed effects of the C60-Cis-Pt nanocomplex were more pronounced than the effects of Cis-Pt or C60 fullerene alone in equivalent dose. Conclusion: Treatment with C60-Cis-Pt nanocomplex prolonged the survival of LLC-bearing mice and reduced anemia in LLC-bearing mice.